Conscious Parenting - Anggraeni Dewi, Rani (ACIECE, 2016)
For the past seven years, i have been actively involed in a program called â€œTraining Living Valuesâ€, which provide training for educators working in public schools such us Madrasah and Pesantren. The program specfically focuses on training teachers about Values-based Education in public schools or boarding schools all over Indonesia. Parent-teacher partnership plays a significant role in a childâ€™s education even though parents remain the premary educator. However, in live there was never a formal school to specifically teach prospective parents, is there?